Analyzing trust and security in computing and communications systems - Pathan, Al-Sakib Khan (Chapman and Hall/CRC Press, USA, 2013)
Whether trust should be considered completely within the perimeter of security in computing and communications systems is a debatable issue. In normal human life, we see these two terms go hand in hand to define the relationships we might have with fellow human beings. Trust among people sets the level of security felt by each person involved in various relationships. If person A does not trust person B, person A may not feel secure in the company of person B. Similarly, these terminologies could also retain the same meanings for our modern computing and communications equipments. However, a notable difference is that whereas trust and security are quite interrelated in human-life scenarios; in technical fields, these are considered as two clearly different issues with distinct boundary lines. In computing and communications fields, trust is a kind of vague term that sets the outline of a task or communication event, based on which the operation can be performed. On the other hand, security is a broad concept that ensures communications go forward in a desired manner, maintaining the core aspects of security intact, that is, privacy, authenticity, authority, integrity, and nonrepudiation. The relation between trust and security could be seen in the way that security includes the concept of trust partially, and trust stays as a wrapper before any secure or insecure communication happens within a network of devices.